Origin of carrier lifetime degradation in floating-zone silicon during a high-temperature process for insulated gate bipolar transistor. (2nd November 2020) - Yokogawa, Ryo; Kobayashi, Hiroto; Numasawa, Yohichiroh; Ogura, Atsushi; Nishizawa, Shin-ichi; Saraya, Takuya; Ito, Kazuo; Takakura, Toshihiko; Suzuki, Shinichi; Fukui, Munetoshi; Takeuchi, Kiyoshi; Hiramoto, Toshiro
Abstract: We report on the relationship between carrier lifetime degradation of floating-zone silicon (FZ Si) and the guard ring formation process for silicon integrated gate bipolar transistor (Si-IGBT). A clear carrier lifetime degradation was observed through the guard ring oxidation and annealing processes for Si-IGBT and showed interstitial oxygen (Oi ) concentration dependence, which was obtained by Fourier transform infrared absorption spectroscopy. Based on the carrier lifetime measurements through the step etching of the FZ Si substrate, it has been suggested that the carrier lifetime degradation is not only caused by the Oi itself near the FZ Si surface region but also the other defects induced by the Oi injection. Diffused interstitial Si atoms kicked-out by the Oi into the FZ Si substrate, which has a longer diffusion length than Oi, can be considered to be the origin of the carrier lifetime degradation.